THE HISTORY OF THE ESTABLISHMENT OF LAW NUMBER 9 OF 2013 REGARDING PREVENTION AND ERADICATION OF TERRORIST FINANCING - Listawati Listawati (Fakultas Hukum, Universitas Diponegoro, 2019)
To response to various acts of terror which occurred in various countries, the Financial Action Task Force (FATF) issued a policy in the form of a recommendations that contained a basic framework for the prevention and eradication of criminal acts of terrorist financing that could be universally applied. This implementation of the FATF standard is obligatory for all countries including Indonesia. One component of Indonesia's commitment to implementing the FATF standard is evidenced by the Establishment of Law Number 9 of 2013 concerning the Prevention and Eradication of Terrorist Financing (TPPT Law). In this paper, we will discuss the history of the formation of the TPPT Law detailed with 2 (two) main focuses, namely the process of criminalizing acts of terrorist financing in the TPPT Law and the factors that encouraged the Government of the Republic of Indonesia to draft special regulations related to anti-terrorist financing. The review of the complexity of the two focuses shows the strong commitment of the state to preventing and eradicating terrorist financing crimes